Observation of a gel of quantum vortices in a superconductor at very low magnetic fields - Llorens, J.B.; Embon, L.; Correa, A.; González, J.D.; Herrera, E.; Guillamón, I.; Luccas, R.F.; Azpeitia, J.; Mompeán, F.J.; García-Hernández, M.; Munuera, C.; Sánchez, J.A.; et al. (American Physical Society, 2020)
Fil: Aragón Sánchez, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina